Collaboration among Registered Nurses and Licensed Practical Nurses: A Scoping Review of Practice Guidelines - Dawn Prentice; Jane Moore; Joanne Crawford; Sara Lankshear; Jacqueline Limoges (Hindawi Limited, 2020)
Professional associations, nurse scholars, and practicing nurses suggest that intraprofessional collaboration between nurses is essential for the provision of quality patient care. However, there is a paucity of evidence describing collaboration among nurses, including the outcomes of collaboration to support these claims. The aim of this scoping review was to examine nursing practice guidelines that inform the registered nurse (RN) and registered/licensed practical nurse (R/LPN) collaborative practice in acute care, summarize and disseminate the findings, and identify gaps in the literature. Ten practice guidelines, all published in Canada, were included in the final scoping review. The findings indicate that many of the guidelines were not evidence informed, which was a major gap. Although the guidelines discussed the structures needed to support intraprofessional collaboration, and most of the guidelines mention that quality patient care is the desired outcome of intraprofessional collaboration, outcome indicators for measuring successful collaborative practice were missing in many of the guidelines. Conflict resolution is an important process component of collaborative practice; yet, it was only mentioned in a few of the guidelines. Future guidelines should be evidence informed and provide outcome indicators in order to measure if the collaborative practice is occurring in the practice setting.